Syphilis infection does not affect immunodeficiency progression in HIV-infected men who have sex with men in China. (April 2020) - Huang, Liping; Cheng, Weibin; Han, Zhigang; Liang, Yuanhao; Wu, Hao; Wang, Haiying; Xu, Huifang; Tang, Shixing
Syphilis and human immunodeficiency virus (HIV) co-infection is expected to play a role in HIV-1-related immunodeficiency progression; however, studies involving syphilis/HIV co-infection have not been conclusive. We investigated the factors associated with co-infection of syphilis and HIV and to assess the effect of syphilis on HIV progression in the context of HIV-1 diversity in an observational cohort of 246 newly-diagnosed HIV-infected but antiretroviral therapy-naive men who have sex with men enrolled in Guangzhou, China between 2008 and 2012. CD4+ cell counts of all the participants were measured from the time of diagnosis until 2015 with an average of 32 ± 18 months. Logistic analysis indicated that patients with syphilis/HIV co-infection were more likely to be older with an adjusted odds ratio (AOR) of 2.48 (95% CI: 1.28–4.80) for those aged between 31 and 40 years and 3.20 (1.11–9.22) for those aged ≥40 years as compared to 16–30 year-olds. The AOR of patients infected with HIV-1 CRF07_BC as compared to CRF01_AE was 2.14 (95% CI: 1.01–4.53). Co-infection of syphilis and HIV was associated with lower baseline CD4+ cell count (0.45, 95% CI: 0.22–0.94), but was not associated with HIV disease progression (HR: 1.03; 95% CI, 0.86–1.23) based on Kaplan–Meier analysis. Our results provide new evidence about the interaction between syphilis and HIV and indicate differential rates of immunodeficiency progression as a function of HIV-1 genetic diversity.